A Survey of Spinal Cord Stimulator Use by Chronic Pain Patients While Driving. Issue 5 (11th November 2015) - Simopoulos, Thomas T.; Rosa, Hollisa; Wootton, Joshua; Eichman, Dave S.; Gill, Jatinder S.
Abstract : Objective: The study aims to assess utilization of spinal cord stimulator (SCS) devices while driving a vehicle and potential association with motor vehicle accidents (MVAs). Materials and Methods: A telephone survey study was conducted in two phases, from 2001 to 2008 and from 2009 to 2011. Patients selected for the survey were age 18 or older and at least one year post‐SCS implantation, demonstrating stable analgesic use for at least six months, and reporting a minimum of 50% pain relief and enhancement of activities of daily living. Both phases of the study evaluated for degree of utilization of SCS while driving a motor vehicle as well as associated accidents. Additionally, patients with active SCS use while driving were further asked in the second phase of the study about mileage per week and first activation of the device postimplant. Results: Ninety‐seven percent of the 78 patients contacted were active drivers and of these, 80% reported chronic and consistent use of SCS for the analgesic benefit while operating a motor vehicle. Eleven percent reported MVAs, which were not related to SCS. In the second phase of the study, participants reported a median of 100 miles driven per week with the SCS device on and began use of the device at a median of 21 days postimplant for up to 49 months. Conclusion: Because of the perceived benefits of pain reduction, there is high utilization of active SCS while driving a motor vehicle and that does not seem predispose toward MVAs.